Vaspin promotes insulin sensitivity in elderly muscle and is upregulated in obesity. Issue 1 (April 2019) - Nicholson, Thomas; Church, Chris; Tsintzas, Kostas; Jones, Robert; Breen, Leigh; Davis, Edward T; Baker, David J; Jones, Simon W
Abstract : Adipokines have emerged as central mediators of insulin sensitivity and metabolism, in part due to the known association of obesity with metabolic syndrome disorders such as type 2 diabetes. Recent studies in rodents have identified the novel adipokine vaspin as playing a protective role in inflammatory metabolic diseases by functioning as a promoter of insulin sensitivity during metabolic stress. However, at present the skeletal muscle and adipose tissue expression of vaspin in humans is poorly characterised. Furthermore, the functional role of vaspin in skeletal muscle insulin sensitivity has not been studied. Since skeletal muscle is the major tissue for insulin-stimulated glucose uptake, understanding the functional role of vaspin in human muscle insulin signalling is critical in determining its role in glucose homeostasis. The objective of this study was to profile the skeletal muscle and subcutaneous adipose tissue expression of vaspin in humans of varying adiposity, and to determine the functional role of vaspin in mediating insulin signalling and glucose uptake in human skeletal muscle. Our data shows that vaspin is secreted from both human subcutaneous adipose tissue and skeletal muscle, and is more highly expressed in obese older individuals compared to lean older individuals. Furthermore, we demonstrate that vaspin induces activation of the PI3K/AKT axis, independent of insulin receptor activation, promotes GLUT4 expression and translocation and sensitises older obese human skeletal muscle to insulin-mediated glucose uptake.